Synthesis, Biodistribution and In vitro Evaluation of Brain Permeable High Affinity Type 2 Cannabinoid Receptor Agonists [11C]MA2 and [18F]MA3 - Ahamed, Muneer; van Veghel, Daisy; Ullmer, Christoph; Van Laere, Koen; Verbruggen, Alfons; Bormans, Guy M. (Frontiers in Neuroscience, 2016)
Abstract The type 2 cannabinoid receptor (CB2) is a member of the endocannabinoid system and is known for its important role in (neuro)inflammation. A PET-imaging agent that allows in vivo visualization of CB2 expression may thus allow quantification of neuroinflammation. In this paper, we report the synthesis, radiosynthesis, biodistribution and in vitro evaluation of a carbon-11 ([11C]MA2) and a fluorine-18 ([18F]MA3) labeled analogue of a highly potent N-arylamide oxadiazole CB2 agonist (EC50 = 0.015 nM). MA2 and MA3 behaved as potent CB2 agonist (EC50: 3 nM and 0.1 nM, respectively) and their in vitro binding affinity for hCB2 was found to be 87 nM and 0.8 nM, respectively. Also MA3 (substituted with a fluoro ethyl group) was found to have higher binding affinity and EC50 values when compared to the originally reported trifluoromethyl analogue 12. [11C]MA2 and [18F]MA3 were successfully synthesized with good radiochemical yield, high radiochemical purity and high specific activity. In mice, both tracers were efficiently cleared from blood and all major organs by the hepatobiliary pathway and importantly these compounds showed high brain uptake. In conclusion, [11C]MA2 and [18F]MA3 are shown to be high potent CB2 agonists with good brain uptake, these favorable characteristics makes them potential PET probes for in vivo imaging of brain CB2 receptors. However in view of its higher affinity and selectivity, further detailed evaluation of MA3 as a PET tracer for CB2 is warranted.